2022
DOI: 10.3389/fenrg.2022.1016406
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in computational study and design of MOF catalysts for CO2 conversion

Abstract: Catalytic conversion of the greenhouse gas CO2 into value-added chemicals and fuels is highly beneficial to the environment, the economy, and the global energy supply. Metal–organic frameworks (MOFs) are promising catalysts for this purpose due to their uniquely high structural and chemical tunability. In the catalyst discovery process, computational chemistry has emerged as an essential tool as it can not only aid in the interpretation of experimental observations but also provide atomistic-level insights int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 86 publications
0
2
0
Order By: Relevance
“…Recently, extensive analysis has been performed to comprehend the role of MOF in drug delivery application via experimental techniques, while theoretical aspects were less explored. Computational studies offer atomic-level insights analysis of structure and properties of MOFs, which are difficult to obtain experimentally (Zhang S. et al, 2020;Chen, 2022;Demir et al, 2023). These insights help in understanding the fundamental mechanisms of MOF behavior and optimizing their design for specific drug delivery applications (Erucar and FIGURE 13 (A) Necrosis and apoptosis assays were used to assess the effects of MOFs, MOF-DOX, and MOF-DOX@DPSCM on CAL27 cells in vitro.…”
Section: Computational Analysis Of Metal Organic Framework In Drug De...mentioning
confidence: 99%
“…Recently, extensive analysis has been performed to comprehend the role of MOF in drug delivery application via experimental techniques, while theoretical aspects were less explored. Computational studies offer atomic-level insights analysis of structure and properties of MOFs, which are difficult to obtain experimentally (Zhang S. et al, 2020;Chen, 2022;Demir et al, 2023). These insights help in understanding the fundamental mechanisms of MOF behavior and optimizing their design for specific drug delivery applications (Erucar and FIGURE 13 (A) Necrosis and apoptosis assays were used to assess the effects of MOFs, MOF-DOX, and MOF-DOX@DPSCM on CAL27 cells in vitro.…”
Section: Computational Analysis Of Metal Organic Framework In Drug De...mentioning
confidence: 99%
“…In order to clarify the catalytic mechanism, activation energy of processes, and information about the active site, cluster-based density functional theory (DFT) simulations have been frequently employed by many researchers. [128,129] In a study by Feng et al, related to ZIF-67 derived nanocarbon composite, DFT simulations suggested that oxygen, HMF, and methanol molecules are adsorbed and activated on CÀ N materials. [130]…”
Section: Impact Of Mofs Properties On Biomass Conversionmentioning
confidence: 99%